Protecting the right to freedom from discrimination in Zambia: Understanding the constitutional and legislative grounds. Issue 3 (September 2019) - Mujuzi, Jamil Ddamulira
The Constitution of Zambia prohibits discrimination in different articles and the grounds on which a person may not be discriminated against are included in two different constitutional provisions – Article 23(3) and Article 266. Apart from the Constitution, some pieces of legislation prohibit discrimination and provide for grounds against which a person may not be discriminated against which are not provided for in the Constitution. Jurisprudence from Zambian courts has not been consistent on the question of whether the list of the grounds against which a person may not be discriminated against is exhaustive. With the exception of the ground of disability, the Constitution does not define the other grounds on which a person may not be discriminated against. In this article, it is argued, inter alia, that the existence of two constitutional provisions providing for different grounds could create uncertainty among some litigants and judicial officials and that in cases where the Constitution does not define the grounds of discrimination, courts could resort to relevant case law, legislation or dictionaries to define such grounds.